Meningkatkan Hasil Belajar Seni Tari Melalui Pendekatan Saintifik di Kelas XI Bahasa - Annisa Maulitu Zahra; Susmiarti Susmiarti (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to describe the use of a scientific approach to the academic achievement of SMA N 1 V Koto Kampung Dalam students in the field of dance. This type of research is classroom action research or classroom action research. This research uses in two stages, namely planning, implementation, observation and reflection. Research tools are observation charts and direct experiments. Data was collected through literature research, observation, tests and documentation. The data is analyzed by a percentage formula. The scientific approach in dance education makes learning very effective, active and fun. Dance learning with a scientific approach can increase student enthusiasm and creativity, it can be seen from the addition of student learning activities with general indicators of student learning activities increasing each meeting with an average percentage of student achievement. at the 1st meeting 49.6% with poor criteria, at the 2nd meeting the average number of students with less good criteria was 61.3% and at the 3rd meeting it rose to 62.7% with quite good criteria After the second period, student learning outcomes rose at each meeting, the average percentage of student learning outcomes at meeting I was 71.7% very good, at meeting II it rose to 76.5% very good criteria.